Pentingya Memanage Keanekaragaman/Diversity dalam Organisasi di Era Blobal - Noermijati (Jurnal Aplikasi Manajemen, 2009)
Organization in the global era, are very close to diversity. It is because the existence of the high inter-dependencies of the organization to others. Diversity existence in the organization must be managed in a good and clear way, and this condition will give highest values to organization, employer, employee, and also to community. Before managing diversity, managers of the organization should understand the trigger or the source of the diversity in the organization. There are three steps to manage diversity in the organization. The first step is by developing multi cultural organization. The second step is by doing the individual approach, and the third step is by executing the organizational approach.